The intraoperative examination of axillary sentinel nodes - Viale, Giuseppe (Radiology and oncology (Ljubljana), 2000)
Routine histological examination of axillary sentinel nodes predicts the nonsentinel axillary node status and may allow to spare axillary clearing in patients with breast cancer. To avoid the need for two separate surgical sessions the results of sentinel node examination should be known intraoperatively. Routine frozen section examination of sentinel nodes, however, is liable to yield false-negative results. An extensive intraoperative examination of frozen sentinel nodes which would attain a sensitivity comparable to that obtained by routine histological analysis has been therefore devised. The frozen sentinel nodes are subserially sectioned at50 microm intervals. For each level, one section is stained with hematoxylinand eosin (H&E) and the other immunostained for cytokeratins using a rapid immunocytochemical assay. Immunocytochemistry did not increase the sensitivity of the examination. The general concordance between sentinel and axillary node status was 96.7%; the negative predictive value of intraoperative sentinel node examination was 94.1%. The intraoperative examination of axillary sentinel nodes is effective in predicting the axillarynode status of breast cancer patients and it may be instrumental in making the decision to spare axillary clearing.
Keywords: Axilla; bezgavke; Biopsy; Breast neoplasms; diagnostika; dojke; Immunohistochemistry; Intraoperative period; kirurško zdravljenje; Lymph node excision; Lymph nodes; Lymphatic metastasis; Pathology; rak (medicina); Surgery